ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN PENJUAL KERBAU DI PASAR HEWAN BOLU KECAMATAN TALLUNGLIPU KABUPATEN TORAJA UTARA - Suprianto Suprianto; Astati Astati (State Islamic University (UIN) Alauddin, 2016)
Sponge animal market is located in the tourist center of Toraja, Rantepao City, Bolu market already well known as an attractive tourist destination and a unique place to visit. Cattle market, so the market is also known, is a sales center buffalo. Sponge animal market as marketing services should attach great importance to customer services, it dikarena sponge animal market is the only market that is the largest animal ditana Toraja. The buyer need to buy livestock covering the needs of the funeral, to be kept back, marriage ceremony and celebration for families who return from overseas. Services are less well able resulted in revenue would be reduced because consumers will seek out livestock animal markets sponge due to inferior services to consumers / communities. Therefore, there will be a study entitled